GAMBARAN PENGETAHUAN, SIKAP, DAN TINDAKAN PEKERJA PADA BAGIAN PRODUKSI MENGENAI PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) DI PT. TOBA PULP LESTARI PORSEA TAHUN 2012 - Yossi Elisabeth Simanjuntak; Halinda Sari Lubis; Arfah Mardiana Lubis (Lingkungan dan Kesehatan Kerja, 2012)
Descriptive of Knowledge, Attitude and Practise of the Workers at the Production Section About the Implementation of The Occupational Safety and Health Management System (SMK3) in PT Toba Pulp Lestari Porsea Year 2012. The Occupational Safety and Health Management System (SMK3) is the part that can not be separated from the other management activity in an institution of work site or a company, such as production management, human resource management, financial management, etc. This research aims to know the description of knowledge, attitude and workers practices on the production section about the implementation of The Occupational Safety and Health Management System (SMK3) in PT. Toba Pulp Lestari Porsea with descriptive research design. The population of this research was all the workers who work in production section counted 374 people and the samples was taken with proportional random sampling technique from the population that is also the workers who work in production section with amount 80 people. According to the result of this research, that knowledge of the worker about the implementation of The Occupational Safety and Health Management System (SMK3) reside in the good category that is counted 80 people (100 %), the worker attitude about the implementation of The Occupational Safety and Health Management System (SMK3) reside in the favorable category that is counted 80 people (100 %) and worker practice about the implementation of The Occupational Safety and Health Management System (SMK3) reside in the good category that is counted 80 people (100%). It is a recommendation to improving the supervision and development in order to apply The Occupational Safety and Health Management System (SMK3) and to optimize the implementation of The Occupational Safety and Health Management System (SMK3) through training and education. Keywords : Labor, Knowledge, Attitude, Practice, SMK3